Non-destructive evaluation of masonry materials used in historic Philippine structures - Peralta, Mathew Harvey T.
The Philippines is a country proud of its colorful culture and history. Integral to these are different heritage structures found in almost every part of the nation. These structures include famous Spanish-era churches such as the Manila Cathedral and the Paoay Church, ancestral homes, and other historical edifices such as the Fort Santiago in Intramuros. Due to the time when which these structures were built, they are commonly made of masonry materials such as adobe, clay bricks, ganites, and the like. The behavior and mechanical characteristics of these materials from that era are seldom known, and the traditional method of knowing is by destructive methods. Since these structures are of cultural importance, these traditional methods cannot be employed. Therefore there is a need for the evaluation of these materials, and consequently the structures built from such, in a non-destructive manner. This study aims to conduct ultrasonictesting and determine different ultrasonic wave characteristics such as pulse velocity, wave attenuation, and frequency through different masonry materials used in Philippine structures. It aims to correlate these non-destructive test parameters to mechanical properties such as uniaxial compressive strength and Young's Modulus of Elasticity determined from destructive testing of the materials. The results showed that ultrasonic pulse velocity and attenuation characteristics are good parameters of the material properties, as seen in their average R2 values ranging from about 0.70 to 0.90. Also, by testing blind samples for verification, it was shown how the size and method of testing affects the results predicted by the equations. The results of this study, coupled with in situ nondestructive testing, can be used to model and analyze the structural behavior of the structures which is necessary in the process of their preservation and rehabilitation.